Application of the protection motivation theory in predicting wild mushroom consumption among university students in China - Si Chen; Yu Chen; ZhenYi Li (PLoS ONE, 2025)
Background Wild mushroom poisoning represents a significant public health challenge in China, with the highest mortality rate globally. Despite extensive prevention campaigns, consumption behaviors persist, particularly among university students who may be influenced by social media and peer pressure. Objective This study applied Protection Motivation Theory (PMT) to investigate psychological factors influencing wild mushroom consumption intentions among Chinese university students and identify key predictors for targeted intervention development. Methods A cross-sectional survey was conducted among 216 Chinese university students. The PMT model included threat appraisal (perceived severity, susceptibility, benefits, costs) and coping appraisal (response efficacy, self-efficacy, response costs). Behavioral intention was assessed through scenario-based consumption likelihood measures. Structural equation modeling was used to test the theoretical model. Results The PMT model demonstrated good fit (χ²/df = 2.14, CFI = 0.94, TLI = 0.92, RMSEA = 0.073, SRMR = 0.065) and explained 42.3% of the variance in wild mushroom consumption intentions (R² = 0.423, 95% CI [0.35, 0.49]). Perceived benefits emerged as the strongest positive predictor (β = 0.385, 95% CI [0.27, 0.50], p < 0.001), while self-efficacy was the strongest negative predictor (β = −0.298, 95% CI [−0.42, −0.18], p < 0.001). Traditional threat appraisal components (severity and susceptibility) showed minimal predictive effects. Response costs also significantly predicted consumption intentions (β = 0.156, 95% CI [0.04, 0.27], p < 0.01). Conclusions PMT provides a valuable framework for understanding wild mushroom consumption behavior among Chinese university students. The dominance of perceived benefits and self-efficacy as predictors suggests that effective interventions should address positive outcome expectations while building confidence in avoidance behaviors. These findings indicate that effective interventions must move beyond traditional risk communication to address the complex interplay of perceived benefits, self-efficacy, and social factors driving consumption decisions, with implications for developing culturally-tailored, multi-component prevention strategies.